Keanekaragaman Jenis dan Kepadatan Zooplankton di Perairan Pulau Makassar Kota Baubau - Ismail Failu; Azelia Monica Azizu; Kasman Kasman; Sofyan Sofyan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
The purpose of the study was to determine the type and amount of zooplankton in the waters of Makassar Island, Baubau City. From the results of this study, it is expected that significant information regarding the types and zooplankton found in the sea around Makassar Island, Baubau City, whose waters are suitable for aquaculture. Furthermore, it is hoped that the results of this study can help improve and optimize the use of aquatic biological resources in the future. This research was conducted in the waters of Makassar Island, Baubau City, from August to October 2021. Sample identification was carried out at the Biology Laboratory of the Muhammadiyah University of Buton. The tool in this research field is plankton net no. 25 to filter zooplankton, GPS determines the sampling location, thermometer measures temperature, handrefactometer measures salinity, DO (Dissolved Oxygen) meter measures sea air oxygen, plastic bottles store seawater samples, small plastic bottles store zooplankton samples, and cool boxes for storing samples. Materials in the field are label paper and markers to label the sample, 70% alcohol to preserve the sample, and aqua water to sterilize the instrument. 1) From the three highest locations found 18 genera of zooplankton belonging to the Crustacea group. 2) With 33 ind/l, the genus OIthona dominates the waters of Makasar Island, Baubau City. 3) In the three locations, there was no variation in zooplankton density.